THE EFFECT OF MEDIA EXPOSURE ON STUDENT MENTAL HEALTH (Proceedings of the International Conference on Education, 2023)
Advances in technology combined with the emergence of the proliferation of social media have facilitated public access to all information to find out. Students are active users of technology and social media. As active users, many students are exposed to social media which can cause worry and fear if they experience similar incidents in the future, causing stress and mental health problems. This study aims to find out how social media is exposed to students' mental health. The theory used in this study is social media literacy and media analysis models. With social media literacy skills, students not only know how to retrieve and process information appropriately in various social settings but can maintain mental health in dealing with excess and uncertainty of information. The research methodology used is quantitative with experimental methods on two groups of students who experience mental health disorders. The results showed that media exposure had a significant effect on students' mental health. Students admit that they are easily influenced by social media. This is shown by the ease with which their moods change after reading information from social media. Students are also addicted to social media, so they lack sleep. Another effect is that they easily doubt, lack confidence, and feel imperfect after reading posts on social media.
Keywords: Media Exposure; Mental Health; social media